A swim-specific shoulder strength and conditioning program for front crawl swimmers - Bradley, J.; Kerr, S.; Bowmaker, D.; Gomez, J.-F. (Strength and Conditioning Journal, 2019)
Although swimming is a whole-body activity, shoulder problems can be quite common in competitive swimmers. The propulsion for swimming comes largely from the upper body but the lower body and trunk play an important supporting role. The swimming shoulder kinetic chain (sskc) describes the generation of swimming propulsion using the whole body. Effective swimmers will use the sskc in their stroke, so effective strength and conditioning programs should also include the sskc. A series of swim-specific exercises using the sskc are presented that focus on the shoulder but can form the basis of a whole-body swimming strength and conditioning program.